Liberal feminism aspects reflected by the character of Queen Elizabeth II in The Crown Season 1 - Fachrul Nuansa Ilham (Passage: Journal of English Language and Literature, 2023)
Liberal feminism is the branch of feminism that believes that men and women are equal. It holds that women can act on the same level as men. It has been a recurring issue in various literary works that features a main female character, especially in film. In addition, liberal feminism can be observed in TV series. A series that portrays a female character is The Crown. This research seeks to investigate what aspects of liberal feminism are represented by the character of Queen Elizabeth II in the first season of the series. This research employed qualitative design due to the descriptive nature of the research that explores a social phenomenon. The theory of liberal feminism by Rosemarie Tong (2018) was also utilized to help analyze and describe Queen Elizabeth II’s behavior which reflected the aspects of liberal feminism. The findings of this study revealed that Queen Elizabeth in this series displays action that falls under the three aspects of liberal feminism, equal education, liberty, and rights. This shows that liberal feminism can also manifests in the behavior of a prominent female historical figure.